Overcoming the efficiency paradigm—The challenges of introducing local organic beef in canteens - Schäfer, Martina; Haack, Michaela (Frontiers in Sustainable Food Systems, 2023)
Introduction In recent years, there has been a growing recognition that public canteens can play an important role in supporting the transformation toward sustainable food systems and providing access to sustainable and healthy food for everybody—including the most vulnerable groups of the population. One important way in which canteens can contribute to this transformation is by increasing the share of organic and local products. These new political and public demands contrast with the organizational development of canteens over the past few decades, which has mainly been characterized by an increase in economic efficiency and a reduction in costs. Based on a project that was carried out in the Berlin-Brandenburg region (Germany), this paper exemplifies some of the challenges canteens face in the process of introducing organic and local products. Methods The empirical results are based on 31 qualitative interviews with canteen managers and kitchen staff as well as with the processing company involved. In addition, a survey of 500 canteen guests was conducted in the participating canteens. Results The analysis shows that the canteens had to adapt various organizational practices to ensure a healthy and sustainable diet at manageable cost. Introducing local organic beef in the canteens requires close cooperation with local farmers and processors, a change in procurement practices, transparency around the origin of the products, as well as adapted menu planning. Discussion Based on the empirical results, the paper discusses how these challenges can be met and which supportive measures can be taken on different governance levels. To change entrenched practices, process facilitators who support local cooperation along the value added chain are needed, and practical knowledge and professional training must be provided. The article concludes that there is a great potential to foster a sustainable and healthy diet via public and private canteens if the tension between efficiency and sustainability orientation can be overcome by adapting framework conditions.